Dobór zmiennych do oceny pracy gimnazjów - Chodakowska, Ewa (Variables selection for assessment of grammar schools, 2006)
This article discusses the issue of grammar schools’ classification and their rankings. Firstly, there have been presented difficulties of data gathering process. On the basis of the collected data of Białystok grammar schools there have been identified main factors differentiating them. The factor analysis and the graphic method that presents the structure of multidimensional data on the plane have been carried out. The research has indicated five fields that should be taken into consideration while describing each school i.e.: the students’ family environment, teaching disabled students, eXams results, type of school and sport competition results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 415-423